2017
DOI: 10.1021/acsami.7b03052
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Continuous Conductive Nanostructure for Highly Sensitive and Stretchable Strain Sensor

Abstract: The demand for wearable strain gauges that can detect dynamic human motions is growing in the area of healthcare technology. However, the realization of efficient sensing materials for effective detection of human motions in daily life is technically challenging due to the absence of the optimally designed electrode. Here, we propose a novel concept for overcoming the intrinsic limits of conventional strain sensors based on planar electrodes by developing highly periodic and three-dimensional (3D) bicontinuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
137
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 59 publications
1
137
0
Order By: Relevance
“…This has been proven to be difficult 9,20,22,34,35 because large stretching requires structural integrity, whereas substantial changes in the electrically active area are required in order to achieve high sensitivity 36,37 . However, several studies have shown that this is possible with highly sensitive piezoresistive structures 11,13,16,20,34,38,39 , but these sensors often show high contact resistance further limiting their feasibility to wearable sensing. Additional functionalities by fabricating transparent 14,16,19,26,27 , self-healing 40 , self-powered 3,41 , tunable 13,17,19,42 , multidimensional 7,12 and multisensing (strain, pressure, temperature, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been proven to be difficult 9,20,22,34,35 because large stretching requires structural integrity, whereas substantial changes in the electrically active area are required in order to achieve high sensitivity 36,37 . However, several studies have shown that this is possible with highly sensitive piezoresistive structures 11,13,16,20,34,38,39 , but these sensors often show high contact resistance further limiting their feasibility to wearable sensing. Additional functionalities by fabricating transparent 14,16,19,26,27 , self-healing 40 , self-powered 3,41 , tunable 13,17,19,42 , multidimensional 7,12 and multisensing (strain, pressure, temperature, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that this is possible with highly sensitive piezoresistive structures 11,13,16,20,34,38,39 , but these sensors often show high contact resistance further limiting their feasibility to wearable sensing. Additional functionalities by fabricating transparent 14,16,19,26,27 , self-healing 40 , self-powered 3,41 , tunable 13,17,19,42 , multidimensional 7,12 and multisensing (strain, pressure, temperature, etc.) 3,4,6,10,21,29,32,33,43,44 strain sensors have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–9 ] On the basis of different mechanisms, flexible strain sensors can be divided into several types including piezoresistivity, capacity, and piezoelectricity. [ 10–14 ] The piezoresistive strain sensors are unquestionably promising candidates for wearable and real‐time human motion‐detecting devices, [ 15,16 ] and they can be sensitive enough for even 10 nm vibration, [ 17 ] but the piezoelectric sensors are more prospective for self‐powered devices owing to the piezoelectric effect of materials, defined as the occurrence of polarization when the material is subjected to external stress as a result of the separation of the positive and negative gravity centers of the molecules. Lead zirconate titanate (PZT) and polyvinylidene fluoride (PVDF) are the most commonly used piezoelectric mediums for piezoelectric sensors due to their high piezoelectric coefficients ( d 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since conventional magnetic particle testing (MT), penetrant testing (PT), and ultrasonic testing (UT) methods are difficult for precise large‐scale infrastructure diagnosis, many techniques were proposed on this topic in recent years, such as sensing techniques of electrical resistance or capacitive MEMS strain sensors and piezoelectric sensors were proposed for precise strain or anomaly detection, but these methods still had limitations for strain imaging on real world structures due to the sensor scale and/or spatial resolution . On the other hand, new types of sensors based on photoelectric methods such as assembled nanowires/nanotubes or microstructured rubber layers, stretchable and flexible strain sensor with conductive nanostructure for sensitive detection of human motion, piezotronic/piezo‐phototronic‐effect enhanced light emitting smart sensors, and flexible or bionic mechanosensors were proposed as effective sensing techniques for dynamic imaging of pressure or stress and diagnosing movement disorders in high‐resolution . However, fabrication methods of the abovementioned nanowire array or flexible smart sensors are complicated, and they are inconvenient for scalable precise stress/strain imaging and especially difficult for large‐scale application and onsite real world infrastructures.…”
Section: Introductionmentioning
confidence: 99%